Diseño de un modelo de trazabilidad para la cadena productiva de carne bovina dela ESPAM-MFL - Carreño Galárraga, Gabriel Eduardo (2014)
This thesis work is to design a model of traceability for beef production chain of ESPAM-MFL, allowing quality control in the manufacturing process of the product, from primary production to distribution, including the processing and production stages. Also help to track and to remove the product from the market if there arises a “Food Alert”. To do this, a system of recording and tracking data from the three links that make up the production chain, that is to say, at the farm, slaughterhouse and meat processing workshop was implemented. This system will record, produce and manage information about the care and welfare of the animal. Following this, we also implemented an identification system "Labels with Barcode" having encoded data such as: Birthplace of the animal, place of slaughter, the animal identification number, date of manufacture, date of expiration, among others, and will link the information registered with the merchandise. The registration and identification system will allow that, there is a link between the flow of goods and information flow to keep traceability at any point.